+0  
 
0
319
1
avatar

Abs(2v+3)=Abs(2v+6)

Guest Sep 15, 2014

Best Answer 

 #1
avatar+87301 
+5

Take both things out of the absolute value bars and solve two equations

2v + 3  = 2v + 6         and        -(2v + 3) = 2v + 6

The first equation has no real solutions

For the second, we have

-2v - 3  = 2v + 6           subtract 2v from both sides and add 3 to both sides

-4v = 9                         divide both sides by -4

v  = -9/4   = -2.25

Here's a graph of the solution using "x" imstead of "v"......  https://www.desmos.com/calculator/zdbtixc1np

CPhill  Sep 15, 2014
 #1
avatar+87301 
+5
Best Answer

Take both things out of the absolute value bars and solve two equations

2v + 3  = 2v + 6         and        -(2v + 3) = 2v + 6

The first equation has no real solutions

For the second, we have

-2v - 3  = 2v + 6           subtract 2v from both sides and add 3 to both sides

-4v = 9                         divide both sides by -4

v  = -9/4   = -2.25

Here's a graph of the solution using "x" imstead of "v"......  https://www.desmos.com/calculator/zdbtixc1np

CPhill  Sep 15, 2014

15 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.